DEMOGRAPHIC AND MORPHOLOGIC CHARACTERISTICS OF BONE METASTASES – 11 YEARS SINGLE CENTER EXPERIENCE - Janevska, Vesna; Samardziski, Milan; Jovanovic, Rubens; Nikolova, Dafina; Pandilov, Stefan; Karanfilovski, Vlatko (Journal of Morphological Sciences; Vol 4 No 1 (2021): JMS, 2021)
This is an epidemiological study of bone metastasis (BM) diagnosed and treated in a period of 11 years. Age and sex distribution of BM, localization, origin of primary malignancy, plain radiography appearance, therapeutic options and survival of the patients were evaluated.  Of 86 patients, 52 were female and 34 male, ranging in age from 44 to 87 years.  The most common site of BM was femur, followed by spine and humerus, and the most common primary malignances were in the breast, lung, kidney and prostate, respectively. Almost one third of patients were with unknown primary malignancy at the time of BM diagnosis.The analysis of patientsâ€™ plain radiographies revealed that most BM were osteolytic lesions. Bisphosphonate therapy was applied in only 41.86% of patients, radiotherapy was applied in only 2.33% of patients and combination of bisphosphonates and radiotherapy received 8.14% of patients.The rest of the patients, 47.67%, were treated with symptomatic and/or with systemic therapy according to their primary malignancy.The survival analysis did not show statistically significant influence of any of the analyzed parameters in this study on the survival of the patients. Only 26.74% of patients survived 24 months and the high 73.26% survived 1 to 24 months. Keywords : bone metastases, localization, primary malignancy, radiographic appearance, survival https://doi.org/10.55302/JMS2141065j